Mass spectrometry-guided discovery of novel GCPII inhibitor scaffolds - Wiseman, Robyn; Thomas, Ajit G.; Janiszewski, John; Hoxie, Nate; Lee, Chae Bin; Wu, Ying; Tsukamoto, Takashi; Ye, Lin; Ronzetti, Michael; Shrimp, Jonathan H.; Adderley, Davina; Rai, Ganesha; et al. (Frontiers in Pharmacology, 2025)
IntroductionThere is an unmet need for therapeutics with a novel mechanism to address Q9 symptoms associated with conditions where aberrant glutamatergic neurotransmission is presumed pathogenic. One enzyme of potential relevance is glutamate carboxypeptidase II (GCPII), a brain metallopeptidase with significantly upregulated activity in nervous tissues following neurodegeneration or injury. Current inhibitors are too polar and charged leading to minimal brain penetration necessitating high systemic doses or direct brain injection. Our efforts are focused on identifying new inhibitor scaffolds with favorable brain penetration.MethodsHerein, we used a newly developed dual-stream liquid chromatography mass spectrometry (LC/MS/MS) substrate cleavage assay to screen two small molecule libraries. The two top confirmed hits were cefsulodin (IC50 = 2 ± 0.1 μM) and amaranth (IC50 = 0.3 ± 0.01 μM). The interactions of Amaranth and cefsulodin with GCPII were characterized with mode of inhibition (MOI) studies, nano differential scanning fluorimetry (DSF) thermal shift assay, and binding site was modeled with in-silico docking. As cefsulodin is an antibiotic used clinically to treat bacterial meningitis, we tested the compound’s brain pharmacokinetics (PK) in mice using a sensitive LC/MS method we developed. Moreover, following confirmation and characterization of cefsulodin and amaranth as viable hits an SAR investigation was conducted with analogs of both compounds.ResultsA first derivative analysis of the DSF data revealed a shift in melting temperature of Δ 0.76 °C (±0.04) for amaranth at 25 μM and 80.41 °C (±0.05) for cefsulodin at 250 μM, suggesting both compounds are acting as stabilizers for the enzyme. Increasing concentrations of cefsulodin increased the Km of N-acetyl-aspartyl-glutamate (NAAG) as a substrate with no change in Vmax, suggesting active site competitive inhibition. In contrast, increasing concentrations of amaranth led to reductions in Vmax while the Km remained constant, suggesting a non-competitive MOI. Results from in-silico docking studies complemented this MOI data, suggesting cefsulodin likely binds in the active site while amaranth likely binds in an allosteric site. Our PK study demonstrated that administration of cefsulodin (100 mg/kg IP) led to a Cmax of 4 μM in the brain, exceeding its GCPII IC50 value.DiscussionOur new screening approaches identified novel inhibitors of GCPII that could serve as molecular templates for further structural optimization.